Acceptability of applying asthma action plan for asthma patients at a hospital in Hochiminh City, Vietnam: an implementation research - Le Thi Kim, Anh; Nguyen Thi My, Linh (Tạp chí Khoa học Nghiên cứu Sức khỏe và Phát triển, 2021)
Objectives: The asthma management strategy at respiratory departments in Vietnam so far does not include the implementation of an asthma action plan (AAP). This study aimed to implement an AAP in the hospital and analyze the acceptability for the implementation procedures of patients, clinicians and asthma management units. Methods: The implementation consisted of 2 phases. Phase 1 was a cross-sectional design that combined quantitative and qualitative methods to assess the asthma control and analyse potential obstacles of the hospital for AAP implementation. Phase 2 was a pre-experimental design to assess the acceptability in implementing the APP. Asthma control was assessed by GINA’s criteria. Implementation strategies included interventions at both organization (issued a procedure and a guideline of consulting the AAP for patients) and individual levels (trained doctors in counseling and monitoring of AAP for patients; provided instruction leaflets of APP for patients). Results: The proportion of asthma sufficient control was 59%, partial control was 30.8%, and insufficient control was 10.2%. Most of obstacles related to asthma management and control were of health facility, such as no concrete procedures in monitoring, insufficiency of infrastructure, overload of patients. Implementation strategies of AAP in this study got the acceptability of patients, clinicians and asthma management units. Conclusion: The study showed the importance of deployment of AAP for asthma patients in Vietnam hospitals. It is essential to provide more staffs for the asthma and COPD management units, especially trained nurses.